Transdimensional epsilon-near-zero modes in planar plasmonic nanostructures - Igor V. Bondarev; Hamze Mousavi; Vladimir M. Shalaev (Physical Review Research, 2020)
We use quantum electrodynamics and the confinement-induced nonlocal dielectric response model based on the Keldysh-Rytova electron interaction potential to study the epsilon-near-zero modes of metallic films in the transdimensional regime. Peculiar effects are revealed such as the plasmon mode degeneracy lifting and the dipole emitter coupling to the split epsilon-near-zero modes, leading to thickness-controlled spontaneous decay with rates increased by up to three orders of magnitude.